2022
DOI: 10.3389/fonc.2022.986762
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of sintilimab plus chemotherapy for advanced or metastatic esophageal squamous cell carcinoma

Abstract: BackgroundSintilimab plus chemotherapy (SIDCHM) is more effective than placebo plus chemotherapy (PLCHM) for advanced or metastatic esophageal squamous cell carcinoma (ESCC). However, considering the high cost of sintilimab, this study evaluated the cost-effectiveness of SIDCHM in comparison with PLCHM for advanced or metastatic ESCC from the Chinese healthcare system perspective.MethodsPolymorphic Markov models were constructed to simulate the course and cost of SIDCHM. Treatment drug costs were calculated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Zhang et al assessed the economics of adding camrelizumab to the first-line chemotherapy from the viewpoint of the Chinese healthcare system and showed that camrelizumab plus chemotherapy was still unlikely to have a cost-effectiveness advantage 20. Four studies evaluated the cost-effectiveness of sintilimab in combination with chemotherapy in the treatment of OSCC in China, and the results of these studies all showed that sintilimab+chemotherapy may be an economical option 30–33. Pembrolizumab is an imported drug, and the price has never decreased since it was launched in China (US$2589.49 per 200 mg).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al assessed the economics of adding camrelizumab to the first-line chemotherapy from the viewpoint of the Chinese healthcare system and showed that camrelizumab plus chemotherapy was still unlikely to have a cost-effectiveness advantage 20. Four studies evaluated the cost-effectiveness of sintilimab in combination with chemotherapy in the treatment of OSCC in China, and the results of these studies all showed that sintilimab+chemotherapy may be an economical option 30–33. Pembrolizumab is an imported drug, and the price has never decreased since it was launched in China (US$2589.49 per 200 mg).…”
Section: Discussionmentioning
confidence: 99%
“…First, the large cost gap and weak survival benefit gap between immunotherapy and chemotherapy lead to higher ICER. In terms of the first-line PD-(L)1 inhibitors in OSCC, most of the published economic studies showed that the incremental QALYs generated by immunotherapy combined with chemotherapy were less than 1 QALY, and only 1 study achieved 1.23 QALYs, while the incremental cost was at least US$7110 and at most US$53 320, resulting in a high ICER 15 20 29–33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the EMPOWER-LUNG 3 trial lacked subsequent regimens after patients entered the PD state, we referred to some studies ( Wu et al, 2020 ; Chen et al, 2022a ; You et al, 2022b ), assuming that patients in both the CCT and PCT groups received the best supportive care (BSC) after their disease progressed until death.…”
Section: Methodsmentioning
confidence: 99%